Analysis of Antimicrobial Efficacy of Triphala and its Effectiveness in Decontaminating the Guttapercha Cones - rana, Manu; Kumari, Shiksha; Upadhyay, Manoj Kumar (Journal of College of Medical Sciences-Nepal, 2018)
Background: -The prime target of endodontic treatment is to maintain an aseptic conditions starting right from the access opening to the obturationof root canals.Many chemicals such as, hydrogen peroxide, chlorhexidineetc have been tried for GP decontamination but none of these compounds have been proven as fully effective.The purpose of this study was to evaluate the effectiveness of an ayurvedic alternative, Triphala for rapid decontamination of guttapercha cones. Materials and Methods: A concentrated extract of triphala was used to check for the antimicrobial efficacy using the agar well diffusion method. Presence of zones’ of diffusion was identified against three common GP contaminants namely, E.coli, E.faecalis and Staph. aureus. New GP Cones, freshly taken out of the packet were then decontaminated for 1minute using triphalaand then placed in thioglycolate broth to check for the presence of turbidity.Results: The zones of inhibition on the agar plate were measured as 23mm, 21mm and 24mm respectively. The broth remained clear even after 48 hours of incubation.Conclusion: We conclude that triphala is indeed effective as a GP decontaminant and it holds promising future as a medium for storage of GP cones. Keywords: decontamination; guttapercha cones; triphala.